Território livre de Iracema: só o nome ficou? memórias coletivas e a produção do espaço na Praia de Iracema - Schramm, Solange Maria de Oliveira (2001)
This dissertation deals with the convenient use of a collective memory to legitimize the symbolic construction of the "tradition" of a place. The empirical reference place chosen was Praia de Iracema, located on the seafront of the city of Fortaleza, which has undergone a process of urban requalification to meet the new and growing demands of tourism and leisure. The study was conducted through an interpretive process anchored in the methodological proposal of John B. Thompson and based on a theoretical discussion on the subject. In the light of the knowledge of aspects of the neighborhood's history and the constitution of memories that consecrated it as a playful space in the context of Fortaleza, an analysis of interventions operated in that territory, by the government, in the mid-1990s, was elaborated, seeking to understand the speeches that justify it. The research revealed that the construction of the symbolism of the neighborhood is rooted in the memories of social groups of an economic, political or intellectual elite. Important urban policy decisions were based on the memories of these groups, endorsing them as the "tradition" of Praia de Iracema, to the detriment of the memories of other groups, which were being erased or obscured.